First Report of Maize chlorotic mottle virus Infecting Maize in the Democratic Republic of the Congo - Lukanda, M.; Owati, A.; Ogunsanya, P.; Valimunzigha, K.; Katsongo, K.; Ndemere, H.; Kumar, P. Lava (Scientific Societies, 2014)
Maize (Zea mays L.) is a major food and fodder crop cultivated on 1.54 million ha in the Democratic Republic of the Congo (DRC). In December 2013, unusually severe chlorotic mottle symptoms and pale green streaks were observed in local varieties (Mudishi 1 and 2, Bambou, Kasayi, H614, H613, and Mugamba) and exotic varieties (H520, H624, H403, HDK8031, and ZM607) in Beni, Lubero, and Rutshuru territories at 1,015 to 1,748 m elevation in North Kivu Province. Symptoms were prominent on newly emerging leaves that later developed marginal necrosis resembling the symptoms of maize lethal necrosis (MLN), caused by a dual infection of Maize chlorotic mottle virus (MCMV, genus Machlomovirus) and Sugarcane mosaic virus (SCMV, genus Potyvirus). Each of these viruses, but particularly MCMV, is also known to cause severe mosaic and mottling symptoms in maize (4). In January 2014, symptomatic and asymptomatic samples (n = 20) from disease-affected fields in Beni and Lubero provinces were collected for virus testing using Whatman FTA Classic Cards (1) and analyzed for MCMV (2681F: 5?-ATGAGAGCAGTTGGGGAATGCG and 3226R: 5?-CGAATCTACACACACACACTCCAGC) and SCMV (8679F: 5?-GCAATGTCGAAGAAAATGCG and 9595R: 5?-GTCTCTCACCAAGAGACTCGCAGC) by reverse transcription (RT)-PCR (4). Samples were also analyzed for Maize streak virus (MSV, genus Mastrevirus), an endemic virus in DRC, by PCR using MSV specific primers (MSV215-234: CCAAAKDTCAGCTCCTCCG and MSV1770-1792: TTGGVCCGMVGATGTASAG) (3). A DNA product of expected size (~520 bp) resulted only for MCMV in all the symptomatic plant samples. None of the samples tested positive for SCMV or MSV. RT-PCR analyses were performed to ascertain the absence of potyviruses using the degenerate potyvirus primers (CIFor: 5?GGIVVIGTIGGIWSIGGIAARTCIAC and CIRev: 5?ACICCRTTYTCDATDATRTTIGTIGC3?) (2) were also negative. Occurrence of MCMV in symptomatic samples was further confirmed by antigen-coated plate (ACP)-ELISA using anti-MCMV rabbit polyclonal antibodies produced at the Virology Unit, IITA, Ibadan, Nigeria. The RT-PCR product of MCMV was purified and sequenced in both directions (GenBank Accession No. KJ699379). Pairwise comparison of 518 bp nucleotide sequence corresponding to p32 and p37 open reading frames of MCMV by BLASTn search revealed 99.8% nucleotide sequence identity with an MCMV isolate from Kenya (JX286709), 98 to 99% identity with the isolates from China (JQ982468 and KF010583), and 96% identity with the isolates from the United States (X14736 and EU358605). MCMV is a newly emerging virus in Africa, first detected during a severe MLND outbreak in 2011 in Kenya (4). This disease has since become a serious threat to maize production in East Africa. MCMV has been reported in maize from Kenya, Rwanda, Tanzania, and Uganda. To our knowledge, this is the first report of MCMV occurrence in DRC. This finding confirms the further geographic expansion of MCMV and illustrates the need for further studies to identify vectors and also create awareness about the disease and to strengthen surveillance to prevent its further spread in the continent.